Impaired CBS-H2S signaling axis contributes to MPTP-induced neurodegeneration in a mouse model of Parkinson’s disease - Yuan, Yu-Qing; Wang, Ya-Li; Yuan, Bao-Shi; Yuan, Xin; Hou, Xiao-Ou; Bian, Jin-Song; Liu, Chun-Feng; Hu, Li-Fang (Brain, behavior, and immunity, 2018)
•Plasma and striatal sulfide levels were decreased in MPTP-induced PD mouse model.•CBS expression was reduced in the striatum and glial cells of MPTP-treated mice.•Striatal CBS overexpression rescued MPTP-induced motor deficits and DA neuron losses.•CBS overexpression reduced the MPTP-induced nitrative stress and α-syn nitration.•Glia CBS overexpression offered both direct and indirect protection to DA neurons. Hydrogen sulfide (H2S), a novel neuromodulator, is linked to the pathogenesis of several neurodegenerative disorders. Exogenous application of H2S exerts neuroprotection via anti-inflammation and anti-oxidative stress in animal and cellular models of Parkinson’s disease (PD). However, the role of endogenous H2S and the contribution of its various synthases in PD remain unclear. In the present study, we found a decline of plasma and striatal sulfide level in 1-methy-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) induced PD mouse model. Interestingly, among the three H2S generating enzymes, only cystathionine β-synthase (CBS) expression was largely reduced in the striatum of MPTP-treated mice. The in vitro study confirmed a significant decrease of CBS expression in 1-methyl-4-phenylpyridinium (MPP+)-stimulated astrocytes and microglia, but not in neurons or SH-SY5Y dopaminergic cells. Striatal CBS overexpression, elicited by stereotaxic delivery with Cbs gene using recombinant adeno-associated-virus (rAAV-Cbs), successfully enhanced the sulfide level in the striatum and partially rescued the MPTP-induced dopaminergic neurotoxicity in the midbrain. Specifically, striatal CBS overexpression alleviated the motor deficits and dopaminergic neuron losses in the nigro-striatal pathway, with a concomitant inhibition of glial activation in MPTP-treated mice. Furthermore, compared to rAAV-Vector, rAAV-Cbs injection reduced the aberrant accumulation of nitric oxide and 3-nitrotyrosine (an indicator of protein nitration) in the striatum of MPTP-treated mice. Notably, it also attenuated the increase of nitrated α-synuclein level in MPTP mice. The in vitro study demonstrated that lentivirus-mediated CBS overexpression elevated the sulfide generation in glial cells. Moreover, glial CBS overexpression offered protection to midbrain dopaminergic neurons through repressing nitric oxide overproduction in both glial and neuronal cells induced by MPP+. Taken together, our data suggest that impaired CBS-H2S axis may contribute to the pathogenesis of PD, and that modulation of this axis may become a novel therapeutic approach for PD.